Occidentalism the West in the eyes of its enemies - Buruma, Ian 1951-; Margalit, Avishai 1939- (Penguin Press, 2004)
"Twenty-five years after Edward Said's Orientalism, a whole field of study has developed to analyze and interpret the denigrating fantasies of the exotic "East" that sustained the colonial mind. But what about the fantasies of "the West" in the eyes of our self-proclaimed enemies? Those remain largely unexamined and, as Ian Buruma and Avishai Margalit argue, woefully misunderstood." "This investigation into the dreams and stereotypes of the Western world that fuel hatred in the hearts of Al Qaeda and its ilk argues that the origins of those dreams lie in the West itself. The anti-Western virus has found a ready host in the Islamic world for a number of reasons, but it is not native there. The West that these jihadis imagine themselves fighting is the same menace that has haunted the thoughts of revolutionary groups since the early nineteenth century. Occidentalism identifies its main oppositions - the timid, soft bourgeois versus the heroic revolutionary; the machine society versus the organically knit one of "blood and soil"; the sterile Western mind, all reason and no soul, versus the "inner life" of the spirit - and provides a new conceptual framework for understanding them, as we must to face the world's most pressing issues."--Jacket